Sobrevivênvia e sucesso de implantes osseointegrados com superfície tratada por ataque ácido: avaliação retrospectiva de 8 a 10 anos - Nícoli, Lélis Gustavo [UNESP] (2014)
Rough-surface dental implants are a viable clinical alternative for rehabilitation of edentulous areas. However, previous studies have suggested that a vast array of risk factors may compromise the long-term success rate of dental implants. This retrospective study aimed to evaluate the survival and the success rates of dental implants with an acid-etched surface. 183 implants were performed in 44 patients who received subsequent implant-supported prosthetic treatment between the years of 2003 and 2005. Patient mean-age at the time of implant placement was 50 years. 18 patients were male and 26 female. Clinical and radiographic examination showed that only 5 implants (2,7%) were lost among 4 patients, 1 in the maxilla and 4 in the mandible and that 3 implants (2,0%) were not in function. 155 (87%) of the functioning implants fell under the success criteria employed whereas 20 (11%) of them presented peri-implantitis. Rehabilitation included screw-retained or cemented single crowns and bridges. A higher prevalence of peri-implantitis (15.3%) was noted for screw-retained bridges. Results showed a survival rate of 97,3% and a success rate of 87% for dental implants with an acid-etched surface after 8 to 10 years of loading.